Antiphospholipid syndrome in 2014: more clinical manifestations, novel pathogenic players and emerging biomarkers - Meroni, Pier Luigi (BioMed Central, 2014)
The clinical spectrum of the anti-phospholipid syndrome (APS) is not limited to vascular thrombosis or miscarriages but includes additional manifestations that cannot be explained solely by a thrombophilic state. Anti-cardiolipin, anti-beta(2) glycoprotein I (anti-β(2)GPI) and lupus anticoagulant (LA) assays are not only the formal diagnostic and classification laboratory tools but also parameters to stratify the risk to develop the clinical manifestations of the syndrome. In particular, anti-β(2)GPI antibodies reacting with an immunodominant epitope on domain I of the molecule were reported as the prevalent specificity in APS patients, correlating with a more aggressive clinical picture. Several laboratory assays to improve the diagnostic and predictive power of the standard tests have been proposed. Plates coated with the phosphatidylserine-prothrombin complex for detecting antibodies represent a promising laboratory tool correlating with LA and with clinical manifestations. Anti-phospholipid antibodies can be found in patients with full-blown APS, in those with thrombotic events or obstetric complications only or in asymptomatic carriers. An inflammatory second hit is required to increase the presence of β(2)GPI in vascular tissues, eventually triggering thrombosis. Post-transcriptional modifications of circulating β(2)GPI, different epitope specificities or diverse anti-β(2)GPI antibody-induced cell signaling have all been suggested to affect the clinical manifestations and/or to modulate their occurrence.